2020
DOI: 10.1186/s12876-020-01278-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between NAFLD and risk of prevalent chronic kidney disease: why there is a difference between east and west?

Abstract: Backgrounds: There is a discrepancy between west and east on the relationship between non-alcoholic fatty liver disease (NAFLD) and chronic kidney disease (CKD). This study aimed to find out the possible reason for this and to clarify the association between NAFLD and CKD by analyzing two population-based datasets from the US and China. Methods: Two health examination datasets from China and the US were used. CKD was defined as an estimated glomerular filtration rate (eGFR) < 60 ml/min/1.73m 2 or and/or abnorm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 29 publications
(32 reference statements)
1
33
0
1
Order By: Relevance
“…Up till now, numbers of studies have explored the relationship between NAFLD and CKD risk in different populations. While numbers of previous studies indicated that the presence of NAFLD was a potential contributory risk factor for the development and progression of CKD, recent studies suggested no adverse association between NAFLD hepatic steatosis and renal function both in general populations and diabetic individuals [19][20][21][22]. Some experts argued that NAFLD itself is not an independent risk factor for CKD, while the comorbidities of NAFLD such as obesity, hypertension, hyperglycemia and hyperuricemia are independently associated with renal dysfunction [23].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Up till now, numbers of studies have explored the relationship between NAFLD and CKD risk in different populations. While numbers of previous studies indicated that the presence of NAFLD was a potential contributory risk factor for the development and progression of CKD, recent studies suggested no adverse association between NAFLD hepatic steatosis and renal function both in general populations and diabetic individuals [19][20][21][22]. Some experts argued that NAFLD itself is not an independent risk factor for CKD, while the comorbidities of NAFLD such as obesity, hypertension, hyperglycemia and hyperuricemia are independently associated with renal dysfunction [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some experts argued that NAFLD itself is not an independent risk factor for CKD, while the comorbidities of NAFLD such as obesity, hypertension, hyperglycemia and hyperuricemia are independently associated with renal dysfunction [23]. Some also argue that NAFLD was associated with early stages of CKD, but not the late stages of CKD [22]. However, most of previous studies had a much higher prevalence of diabetes in their study samples [24,25], raising the possibility of selection bias given the strong association between diabetes and CKD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations